2007
DOI: 10.1007/s10557-007-6074-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of Tako-tsubo Syndrome

Abstract: Tako-tsubo syndrome encompasses heterogeneous patient populations and it is likely that different pathogenic mechanisms may operate in different patients. Treatment of the condition is at present empirical and aimed at preserving ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
0
19
0
4
Order By: Relevance
“…Due to the recent recognition of TTC and its low incidence of diagnosis, as mentioned earlier, only a relatively small number of patients have been studied in a few published series. No large studies have confirmed the etiology of TTC (43). A rapidly accumulating body of evidence has led to very interesting insights into the possible pathophysiology of TTC.…”
Section: Pathogenesismentioning
confidence: 99%
“…Due to the recent recognition of TTC and its low incidence of diagnosis, as mentioned earlier, only a relatively small number of patients have been studied in a few published series. No large studies have confirmed the etiology of TTC (43). A rapidly accumulating body of evidence has led to very interesting insights into the possible pathophysiology of TTC.…”
Section: Pathogenesismentioning
confidence: 99%
“…The precise mechanisms underlying transient LV dysfunction are not yet fully understood, but several possibilities have been proposed [2][3][4][18][19][20][21]. Exaggerated sympathetic stimulation and elevated plasma catecholamines from emotional or physical stress are probably central to the pathophysiology of this cardiac syndrome.…”
Section: Pathophysiology Of Tlvabmentioning
confidence: 99%
“…Mittlerweile wird geschätzt, dass 1-2% aller Patienten mit der initialen Diagnose eines akuten Koronarsyndroms ("acute coronary syndrome", ACS) tatsächlich an einer TK leiden [2,8,16,31,37]. In der Studie von Kurowski et al [20] ließen sich die charakteristischen apikalen Wandbewegungsstörungen des linken Ventrikels bei 60% der untersuchten Patienten beobachten; dahingegen lag bei 40% aller Patienten mit Diagnose einer TK eine mittventrikuläre Wandbewegungsstörung vor.…”
Section: Klinische Symptomeunclassified
“…Aus rein theoretischen Überlegungen favorisieren einige Autoren in Anlehnung an bekannte Therapiealgorithmen der chronischen Herzinsuffizienz bei hämodynamisch stabilen Patienten β-Blocker und Angiotensinkonversionsenzym-(ACE-)Hemmer bzw. Sartane für die Therapie der TK [31,37]. Andere Autoren stehen der Applikation von β-Blockern jedoch kritisch gegenüber [2], da die potenziell unerwünschten Effekte der β-Blockade bei erhöhten Katecholaminspiegeln und nichtblockierten α-Rezeptoren miteinkalkuliert werden müs-sen [2].…”
Section: Verlaufunclassified
See 1 more Smart Citation